P-003 Intracranial Aneurysms in the Youngest Patients: Characteristics and Treatment Challenges. (14th July 2013) - Gross, B; Smith, E; Scott, R; Orbach, D
Abstract : Background: Paediatric intracranial aneurysms have been reviewed in several recent series. These series have included patients up to ages 15–18. However, the characteristics and treatment challenges of aneurysms in young children differ from those in teenagers. As such, we focused on the cohort of children age 10 and under who presented with intracranial aneurysms, and discuss subtypes, presentation, treatment strategies, and outcomes. Methods: With approval from the Boston Children's Hospital Institutional Review Board, the records of children undergoing cerebral or spinal angiography by the senior author (DBO) from October 2006–June 2012 were reviewed to identify patients aged 10 and under who presented with intracranial aneurysm. Presentation, subtype of aneurysm, treatment strategy, and outcome were evaluated. Results: Of 592 paediatric cases reviewed, 27 were for paediatric patients up to age 17 harbouring cerebral aneurysms (4.6%), and 15 occurred in children 10 years of age and younger (2.5%), with a mean age at presentation of 5.1 years (range, 3 months - 10 years). Of these fifteen children, 4 had characteristics of arterial dissection, 3 had angiographic characteristics of pseudoaneurysm (with all three having a history of prior microsurgery for tumour), 4 were fusiform, 3 were saccular (with 1/3 in a patient with PHACES and Moyamoya), and 1 was mycotic. Six patients underwent endovascular treatment, 1 underwent combined microsurgical and endovascular repair and 4 underwent microsurgical repair. Four patients have not been treated and are under current observation. One patient expired due to complications related to prior attempted aneurysm treatment at an outside facility, 1 patient expired from complications related to his malignant brain tumour, and 1 patient experienced complications related to attempted microsurgical repair; the other 11 patients are intact or have neurological compromise related to their initial presentation. Conclusions: Previous investigations, including patients from birth to late teenage years, have documented unique characteristics of paediatric aneurysms relative to adults. We demonstrate that the youngest patients, those age 10 years and under, have aneurysms even more distinct than those in the larger paediatric cohort. These patients present unique treatment challenges. Disclosures: B. Gross: None. E. Smith: None. R. Scott: None. D. Orbach: None.